PRODUCTION OF BEE POLLEN USING POLLEN COLLECTORS IN THE TIMETABLE OF FOOD AVAILABILITY IN THE TOP OF BRACATINGA´S BLOOM (Mimosa scabrella) - Moura, Joelma; Pegoraro, Adhemar (Scientia Agraria, 2006)
In Mandirituba-PR, a city located in southern Brazil, the production of bee pollen in the top of Bracatinga’s bloom was analyzed through the use of pollen collectors in non-continuous system for nine days from 3rd to 23rd August, 2005, the objective was to observe the time of the day that occurs the harvest by Apis mellifera connected to the ambient temperature and humidity. With this purpose were used 12 beehives of Africanized bees, with 9 mounth queens and stimulated with food only from bracatinga’s bloom. The average production observed in the colonies was about 42,84 ± 24,34 mL of bee pollen in a day of collection, and the difference of production between the beehives is due to the bee skills in collect pollen. In sunny days the pollen collectors were activated from 09:48 to 14:26 getting a great production without the necessity of implanting artificial food.